Seroprevalence of Toxoplasmosis in Puerperal Women Treated at a Tertiary Referral Hospital - Juliana Fernandes Medeiros; Ana Cláudia Rabelo e Silva; Natália Domene Franco da Rocha; Alexia Viegas Georg; Patricia Pereira dos Santos Melli; Silvana Maria Quintana; Geraldo Duarte (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To evaluate the seroprevalence of toxoplasmosis among puerperal women cared for at a tertiary university hospital and the level of understanding of these puerperal women about toxoplasmosis, vertical transmission, and its prophylaxis. Methods For this cross-sectional study, we evaluated 225 patients using presential interviews, prenatal documentation, and electronic medical records. Data were stored using Research Electronic Data Capture (REDCap) software. Prevalence rates were estimated by the presence of reactive IgG antibodies against Toxoplasma gondii. Data analysis was performed using the chi-square test and calculation of the odds ratio (OR). Seroreactivity to T. gondii and exposure variables (age, educational level, and parity) were analyzed using a confidence interval (95%CI) and a significance level of 5% (p < 0.05). Results The seropositivity rate for T. gondii was 40%. There was no association between seroprevalence and age. Primiparity was a protective factor against seropositivity and low education was a risk factor. Conclusion Knowledge of T. gondii infection and its transmission forms was significantly limited, presenting a risk for acute maternal toxoplasmosis and vertical transmission of this protozoan. Increasing the education level regarding the risk of toxoplasmosis during pregnancy could reduce the rates of infection and vertical transmission of this parasite.